COVID-19 Knowledge/Practices, Mental Status, and Return-To-Work Concerns Among Healthcare Workers in Huangzhou District, Huanggang City, China - Zheng, Yanfei; Li, Tianxing; Zhang, Ying; Luo, Hui; Bai, Minghua; Liu, Zhenquan; Zeng, Yong; Deng, Guangrui; Xiao, Huiqun; Zhang, Yang; Zhang, Zheng; Chen, Huirong; et al. (Frontiers in Public Health, 2022)
This study investigated the COVID-19-prevention knowledge and practices of healthcare workers (HCWs), HCWs’ psychological state regarding returning to work, and HCWs’ trust in using traditional Chinese medicine (TCM) to prevent and treat COVID-19. A cross-sectional survey was conducted from April 23 to May 14, 2020, with 2050 HCWs from 13 hospitals in Huangzhou District,Huanggang City , Hubei Province, China. In the survey, 47.9% and 46.6% indicated they had very good knowledge and good knowledge of preventative measures, respectively.Multivariable logistic regression indicated that male, tertiary hospital, medical staff, and undergraduate/postgraduate qualification were well correlated with good knowledge.Good knowledge was associated with good practice (OR: 4.451; 95% CI: 2.552–7.763; p<0.01). 59.8% of HCWs reported worries about resuming work; the main reason was asymptomatic infection. The Self-Rating Anxiety Scale (SAS) indicated that 10.8% of participants had mild anxiety, 1.5% moderate anxiety, and 0.1% severe anxiety. Working at Huangzhou District People’s Hospital (the hospital designated for physical examinations of returning workers) and female were risk factors for concerns about resuming work and anxiety symptoms while good knowledge and practice of preventive measures were protective factors. HCWs’ trust in using TCM to treat COVID-19 was significantly higher than their trust in using TCM for prevention (p<0.001). Regarding preferences for preventative TCM products, oral TCM granules were the most preferred (62.4%). HCWs indicated they wanted to know more about the clinical efficacy, applicable population, and adverse reactions of preventative TCM products (89.3%, 81.1%, and 81.4%, respectively). The results suggest that promoting knowledge and practices regarding COVID-19 prevention can help alleviate mental state about returning to work. Further, a need for clinical trials of preventative TCM products to obtain evidence.